2012
DOI: 10.1007/s10792-012-9586-5
|View full text |Cite
|
Sign up to set email alerts
|

Spectral-domain optical coherence tomography of astrocytic hamartomas in tuberous sclerosis

Abstract: Retinal astrocytic hamartomas are benign tumors of the retinal nerve fiber layer (NFL) that may be found in association with tuberous sclerosis (TS). We describe the spectral-domain optical coherence tomography (SD-OCT) features of type 1 astrocytic hamartomas in a child with TS that may aid in the diagnosis and follow-up of these lesions. Gradual, dome-shaped hyper-reflective elevations of the retinal NFL were seen on SD-OCT with subtle shadowing of the underlying tissues. In addition, the vitreous cortex sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…While symptomatic changes to the fundus due to a retinal hamartoma occur in comparatively few cases, there have been some reports of other changes, including subretinal hard exudates, macular edema, vitreous hemorrhage, and exudative retinal detachment [3,4,5,6,7,8,9,10]. This invasive tumorous lesion tends to be limited to the retinal nerve fiber layer (NFL), and when examined by spectral domain-optical coherence tomography (SD-OCT), NFLs are reportedly observed as dome-like ridges of high intensity [11, 12]. In addition, it has also been reported that pathologically, myelin formation and gliosis are observed in this tumor [2].…”
Section: Discussionmentioning
confidence: 99%
“…While symptomatic changes to the fundus due to a retinal hamartoma occur in comparatively few cases, there have been some reports of other changes, including subretinal hard exudates, macular edema, vitreous hemorrhage, and exudative retinal detachment [3,4,5,6,7,8,9,10]. This invasive tumorous lesion tends to be limited to the retinal nerve fiber layer (NFL), and when examined by spectral domain-optical coherence tomography (SD-OCT), NFLs are reportedly observed as dome-like ridges of high intensity [11, 12]. In addition, it has also been reported that pathologically, myelin formation and gliosis are observed in this tumor [2].…”
Section: Discussionmentioning
confidence: 99%
“…The SD-OCT findings of solitary circumscribed retinal astrocytic proliferation are different [8][9][10][11][12][13] than the features of retinal astrocytic hamartoma, which arises in the nerve fiber layer with gentle sloping configuration, and occasionally demonstrate cavitation or "moth-eaten" calcific nodules. 8,9,11,12 The clinical and angiographic features of this condition differ from retinal astrocytoma, which usually manifests a grayyellow color with internal vascularity and retinal exudation.…”
Section: Inmentioning
confidence: 99%
“…8,9,11,12 The clinical and angiographic features of this condition differ from retinal astrocytoma, which usually manifests a grayyellow color with internal vascularity and retinal exudation. The SD-OCT of this condition closely resembles that of congenital simple hamartoma of the RPE with abrupt vertical margins showing derby hat configuration and dramatic posterior shadowing.…”
Section: Inmentioning
confidence: 99%
“…82,86 In contrast, astrocytic hamartomas appear as a hyperreflective mass localized to the RNFL associated with optically empty spaces, focal vitreous adhesions, and a gradual transition between tumor and surrounding normal tissue. 84,85 Retinoblastoma lesions appear isodense or hyperdense on OCT, are associated with patches of calcification, and usually have an abrupt transition toward uninvolved retina, which helps to distinguish them from hamartomas (Fig. 7).…”
Section: Ocular Oncologymentioning
confidence: 99%
“…7). 10,84 The degree of retinal layer involvement is dependent on lesion size, which extends from involvement of the inner nuclear and middle retinal layers in isolation with preservation of the RNFL and ORLs (smaller tumors), to involvement of the full thickness of the retina (larger tumors). 10 Preretinal seeds in retinoblastoma are located superficial to the retina, appear isodense and smooth, and are associated with shadowing of the underlying structures on OCT. 10 Optical coherence tomography is also proving useful with regard to monitoring tumor progression, identifying new lesions and recurrences, monitoring treatment response, and guiding further management.…”
Section: Ocular Oncologymentioning
confidence: 99%